FEATURES OF THE CURRENT LEGISLATIVE REGULATION OF THE PRIMARY RIGHT TO LAND - Rybalko K.V. (Pressing Problems of Public Administration, 2018)
The analysis of the current legislation concerning the implementation of priority rights of certaincategories of citizens to land is made. The main problems that arise during the implementation of thisright are outlined. The directions of further solution of this issue at the state level are determined.